In Silico Prediction of 3D Structure of Pectatelyase from Fusarium oxysporum f. sp. lycopersici - pige, Ramesh K.V2 and Vikram A, Raghavendra Rao B, Manojkumar H. Nagasam (Recent Research in Science and Technology, 2011)
In Silico Prediction of 3D Structure of Pectatelyase from Fusarium oxysporum f. sp. lycopersici